Encapsulation of Heracleum persicum essential oil in chitosan nanoparticles and its application in yogurt - Yousefi, Mojtaba; Khanniri, Elham; Sohrabvandi, Sara; Khorshidian, Nasim; Mortazavian, Amir M. (Frontiers in Nutrition, 2023)
Heracleum percicum essential oil (HEO) at various levels was encapsulated in chitosan nanoparticles and its potential application in yogurt was investigated. The value obtained for encapsulation efficiency, loading capacity, mean particle size and zeta potential of nanoparticles were 39.12-70.22%, 9.14-14.26%, 201.23-336.17 nm and +20.19-46.37 mV, respectively. The nanoparticles had spherical shape with some holes as a result of drying process. In vitro release studies in acidic solution and phosphate buffer solution indicated an initial burst effect followed by slow release with higher release rate in acidic medium. Results of antibacterial activity revealed that S. aureus and S. typhimurium with inhibition zones of 21.04-38.10 and 9.39-20.56 mm2 were the most sensitive and resistant bacteria to HEO, respectively. Incorporation of encapsulated HEO into yogurt decreased pH and increased titratable acidity due to stimulation of starters’ activity. Interaction of nanoparticles with proteins decreased syneresis in yogurt. Regarding antioxidant activity, a higher value was observed in yogurt containing encapsulated HEO after 14 days of storage due to degradation and release of essential oil from nanoparticles. In conclusion, application of HEO nanoparticles in yogurt could be a promising approach for development of functional food products such as yogurt with enhanced antioxidant properties.